Factors Associated with the Implementation of Patient Safety at X Hospital, Karawang, Indonesia - Suryani, Lilis; Kurniawan, Ricky; Perdani, Agni Laili (KnE Life Sciences, 2021)
Patient safety is a significant global health problem and a top priority for incidents prevention. Data revealed that the patient safety goals’ average implementation was only 33.5%, far away from the 100% target. The compliance of hand hygiene among nurses, meanwhile, was only 28.6%. This study aims to analyze factors associated with the implementation of patient safety goals among nurses at X Hospital Karawang. A cross-sectional approach with a simple random sampling technique was implemented in this study. A total of 117 nurses in the inpatient room were recruited in this study. A significant relationship showed knowledge, supervision, motivation, and the implementation of patient safety goals (p-value < 0.05). Supervision from the head nurse is the most associated factor. By improving the quality of Supervision, will influence the application of patient safety goals; therefore, that a patient safety culture is created and achieved well. recommend to define clearly the significant of patient safety and what kind of indicators we can use to measure this? and evaluate qualitatively (not using percetange) to indicate the extent to which patient safety is applied. Keywords: patient safety goals, Supervision, knowledge, motivati